Tackling hepatitis E virus spread and persistence on farrow-to-finish pig farms: Insights from a stochastic individual-based multi-pathogen model - Morgane Salines; Nicolas Rose; Mathieu Andraud (Epidemics, 2020)
Hepatitis E virus (HEV) is a zoonotic agent of which domestic pigs have been recognised as the main reservoir in industrialised countries. The great variability in HEV infection dynamics described on different pig farms may be related to the influence of other pathogens, and in particular viruses affecting pigs’ immune response. The objective of this study was to develop a multi-pathogen modelling approach to understand the conditions under which HEV spreads and persists on a farrow-to-finish pig farm taking into account the fact that pigs may be co-infected with an intercurrent pathogen. A stochastic individual-based model was therefore designed that combines a population dynamics model, which enables us to take different batch rearing systems into account, with a multi-pathogen model representing at the same time the dynamics of both HEV and the intercurrent pathogen. Based on experimental and field data, the epidemiological parameters of the HEV model varied according to the pig’s immunomodulating virus status. HEV spread and persistence was found to be very difficult to control on a farm with a 20-batch rearing system. Housing sows in smaller groups and eradicating immunomodulating pathogens would dramatically reduce the prevalence of HEV-positive livers at slaughter, which would drop from 3.3% to 1% and 0.2% respectively (p-value < 0.01). It would also decrease the probability of HEV on-farm persistence from 0.6 to 0 and 0.34 respectively (p-value < 0.01) on farms with a 7 batch rearing system. A number of farming practices, such as limiting cross-fostering, reducing the size of weaning pens and vaccinating pigs against immunomodulating viruses, were also shown to be pivotal factors for decreasing HEV spread and persistence. Keywords: Hepatitis E virus, Farm-level risk factors, Multi-pathogen model